Relationship of Self-regulation and Lifestyle Behaviour with Overweight Among Male and Female Adolescents in Selangor - Anu Suria Ganason; Noor Azimah Muhammad; Gunenthira Rao; Hizlinda Tohi; Majmin Sheikh Hamzah; Khairani Omar (Malaysian Journal Of Nutrition (MJN), 2024)
Indexed by Scopus/MyCite